From mastery to subjection: An embodied ethics of entrapment in Amazonia - Nahum-Claudel, Chloe (Journal of material culture, 2019)
The Amazonian Enawenê-nawê dam rivers in order to catch shoals of fish. The dam is composed of a weir structure into which humanoid traps are inserted at three underwater levels. The author's analytical focus is on the contrasting forms of life that are shaped by each part of this dialectical technology. As men construct the weir and then tend the traps, the kinds of effort required of them, their relationships to one another, to space, to time, to their aquatic prey and to their ancestors are all reconfigured. Over the course of about two months, men take a subjective journey from mastery to subjection, from engineering a physical technology, to embracing a set of mental and social techniques to animate their traps. The author suggests that the fishermens' patient subjection of their bodies, minds and sociality to their traps speaks more generally to the perils of entrapment, which cannot rest on mastery alone, but must imply subjection and vulnerability.